KUR’AN’I ANLAMA ÇABASI VE YÖNTEM SORUNU -Amine Vedud Muhsin Örneği- - Hafsa Fidan (İslami İlimler Dergisi)
In this article, we will investigate Amina Wadud-Muhsin’s interpretation and hermeneutical model as an example of contemporary Quran interpretations. Wadud aims to interpret Quran and to exceed the tradition by using the hermeneutical model. But first of all the idea of exceed the tradition and read Quran in its context has got some problems. Moreover in this article, Islamic feminist approaches are examined, since Wadud interprets Quran via Islamic feminist prejudices.